Employment effects of investment subsidies by German Regional Policy - Franz-Josef Bade; Bastian Alm; Sebastian Weins (ZBW – Leibniz Information Centre for Economics, 2020)
This study investigates the employment impact of investment subsidies in Germany. With 45 billion Euro for about 100,000 firms since the German reunification, these capital grants are the central element of regional policy for strengthening employment in economically weaker regions. The effects of investment grants are analysed by comparing the employment growth of assisted firms with their counterfactual outcome. The hypothetical growth without grant is estimated with panel data from 1999 to 2009 for each German firm in the social security records which are linked with the official records of investment grants. The control group are selected out of total non-assisted firms by combining covariate and propensity score matching methods. The employment effect is determined by cross-section estimators. The assisted firms show a significantly stronger employment growth than their control group. This result is quite robust. Even if the control group is restricted to those non-assisted firms which have had a similar employment growth before the year of allowance, the differences in the growth after the allowance persist. Further heterogeneity tests do not reveal significant hidden influences. All subgroups analysed show nearly the same growth difference between assisted and non-assisted firms.
Keywords: B41; C14; C21; C81; H71; R00; R11; R28; R58; 330